A Comparative of Job Stress among Nurses in the Intensive Care Unit: Primary Nursing vs. Case Method - Badrabadi, Parvaneh; Nazmieh, Hossein; Nasiriani, Khadijeh (Advances in Nursing & Midwifery, 2024)
Introduction: Healthcare centers have been established with the aim of providing quality, safe, and effective care. In order to achieve these goals, nursing managers have the responsibility to choose a nursing care delivery model that ensures quality and minimizes the job stress of nurses. The objective of this study was to compare the impact of primary nursing and case method on job stress of nurses working in the intensive care unit (ICU). Methods: This was a pilot quasi-experimental study which two nursing care methods, primary nursing and case method, were compared using a pretest-posttest design. The study population consisted of 25 nurses working in the ICU. The data collection tools included demographic questionnaires and an expanded version of the nursing stress scale. The collected data were analyzed using SPSS version 25 and running paired samples t-test. Results: Based on the findings, the demographic characteristics of nurses did not show statistically significant differences between two groups (p > 0.05). The mean total score of job stress for nurses in the case method group (25.12±125.16) was significantly higher than in the primary nursing group (16.07 ± 109.04) (p = 0.009). Conclusions: According to the findings, the provision of nursing care through the primary nursing method reduced job stress among adult nurses in the ICU. Therefore, it is recommended to give more attention to the primary nursing approach in the management planning of nursing care.